2018
DOI: 10.1051/bioconf/20181002001
|View full text |Cite
|
Sign up to set email alerts
|

The effect of conditions and storage time on course of moisture and temperature of maize grains

Abstract: Characteristics of stored cereals significantly affect the technical solution of individual storage facilities, as well as the technical appliances used to provide storage technologies, i.e. storing aeration and off-loading. The objective of the study was to monitor the influence of atmospheric temperature and extraneous moisture on the course of temperature and moisture of maize grain during the storage. An average value of maize grain moisture was 13.6% and an average value of temperature inside of the silo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 18 publications
(29 reference statements)
1
7
0
Order By: Relevance
“…Rice, soybean, and corn grains are processed at a variety of moisture content levels depending on the processing type [14,15]. Different moisture contents are required, for example, for storage (preferably low to reduce the risk of mold development, for rice as low as 9% MC [14], for corn up to 14% MC [20]) and for harvesting (for medium rice about 22-24% MC [15], for corn below 28% MC [21]), and grains with different MC will be suitable, for instance, for comminution or milling (for rice 12-14% MC [14], for corn 14-15% MC [20]). The physical and mechanical properties in this study were analyzed for grains with the MC ranged from 10% to 26%, to cover the MC ranges of grains processing.…”
Section: Introductionmentioning
confidence: 99%
“…Rice, soybean, and corn grains are processed at a variety of moisture content levels depending on the processing type [14,15]. Different moisture contents are required, for example, for storage (preferably low to reduce the risk of mold development, for rice as low as 9% MC [14], for corn up to 14% MC [20]) and for harvesting (for medium rice about 22-24% MC [15], for corn below 28% MC [21]), and grains with different MC will be suitable, for instance, for comminution or milling (for rice 12-14% MC [14], for corn 14-15% MC [20]). The physical and mechanical properties in this study were analyzed for grains with the MC ranged from 10% to 26%, to cover the MC ranges of grains processing.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of Garg et al (2016) revealed that the moisture content of wheat packaged in metallic bins and jute bags responds to environmental moisture change. Angelovič et al (2018) also reported that extraneous temperature and moisture dictate the moisture content of maize stored in a silo. External conditions can also influence condensate formation on the surface of improperly dried grains (Kechkin et al, 2020).…”
Section: Effects Of Temperature and Moisture During Storage Onmentioning
confidence: 95%
“…The results obtained in the characterization of the corn stover ( Oyedeji et al 33 report a moisture content on a dry basis of 15.9%, while Angelovič et al 34 obtained an average moisture percentage of 13.6%. For the pH parameter, Gómora et al 35 recorded 6.77 + 0.053, while Rendón 36 reported a pH of 6.76.…”
Section: Physical-chemical Characterization Of the Wastementioning
confidence: 99%